Food Security Model in North Sumatra Province - Yeni Ariesa; Rafida Khairani (Kusuma Negara Business School, 2020)
This study aims at provide information about the development of food security model in North Sumatra Province. This study was carried out in the districts and the cities. The data have been collected from various institutions from Agricultural Office, Food Security Office and Statical office of North Sumatera province. It also collects secondary data which are covering various aspects of food production, to enrich the study, I have been interviewing stakeholders who responsible to manage food security development. Analysis Confirmatory Factor Analysis Model is used to analyze factors affecting food security The results of the study shows the results of speed analysis in aspects of food production, so far the value of production has always dropped, general production modeling is only 80% and relatively an average of 20% every year which must be issued by import from other countries.